Separation of Vanillin by Perstraction Using Hydrophobic Ionic Liquids as Extractant Phase: Analysis of Mass Transfer and Screening of Ils Via Cosmo-Rs - Romero-Figueroa, J; Quijada-Maldonado, E; Cabezas-Cornejo, R; Araya-Lopez, C; Olea-Chandia, F; Villarroel-Utreras, E (Elsevier B.V., 2021)
This paper presents an experimental and theoretical study for a perstraction system to recover diluted vanillin from aqueous solutions using an organophilic and hydrophobic membrane of polydimethylsiloxane (PDMS), and the hydrophobic ionic liquids (ILs) 1-butyl-3-methylimidazolium bis((trifluoromethyl)sulfonyl)imide ([bmim][Tf2N]), 1-octyl-3-methylimidazolium bis((trifluoromethyl)sulfonyl)imide ([omim][Tf2N]) and trihexyl tetradecyl phosphonium cyanamide ([P6,6,6,14][DCA]) as the extractant phase. The proposed mass transfer model was established as suitable for describing the extraction of vanillin from the aqueous phase in the perstraction system using ILs. According to this model, it was determined that the main mass transfer resistances were offered by the PDMS membrane, followed by the IL. [P6,6,6,14][DCA] experimentally showed a 13% increase in the transmembrane flux in comparison with the [Tf2N] anion based ILs, but also showed higher water transmembrane flux. In this regard, [omim][Tf2N] was found to exhibit better vanillin/water selectivity. The perstraction system gives better transmembrane fluxes than the data reported in the literature for vanillin extraction using pervaporation system. On the other hand, according to the screening in COSMO-RS, the combination of the anions DCA, SCN, TCC, Otf, PFBS, Tf2N, Pf2N y PF6 with pyrrolidinium, piperidinium and phosphonium base cations, are suitable to increase the performance of vanillin extraction. © 2021 Elsevier B.V.